Challenging Multiple-Choice Questions to Engage Critical Thinking - Dennis D. Kerkman; Andrew T. Johnson (Park University, 2014)
This article examines a technique for engaging critical thinking on multiple-choice exams. University students were encouraged to "challenge" the validity of any exam question they believed to be unfair (e.g., more than one equally correct answer, ambiguous wording, etc.). The number of valid challenges a student wrote was a better predictor of exam scores than the number of invalid challenges or GPA. The technique also allows instructors to gain insight into the sources of students' errors that may be useful in improving instruction.